2018
DOI: 10.1016/j.isci.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Ezh1 Targets Bivalent Genes to Maintain Self-Renewing Stem Cells in Ezh2-Insufficient Myelodysplastic Syndrome

Abstract: SummaryPolycomb repressive complex (PRC) 2 represses transcription through histone H3K27 trimethylation (H3K27me3). We previously reported that the hematopoietic-cell-specific deletion of Ezh2, encoding a PRC2 enzyme, induced myelodysplastic syndrome (MDS) in mice, whereas the concurrent Ezh1 deletion depleted hematopoietic stem and progenitor cells (HSPCs). We herein demonstrated that mice with only one Ezh1 allele (Ezh1+/-Ezh2Δ/Δ) maintained HSPCs. A chromatin immunopreciptation sequence analysis revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
(55 reference statements)
6
17
0
Order By: Relevance
“…Previous studies have suggested that EZH1 augments and complements EZH2 activity and partially compensates for its loss in different contexts . We herein demonstrated that H3K27me3 levels were maintained or elevated after TAS‐117 treatment (see the data in Figure B,C).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Previous studies have suggested that EZH1 augments and complements EZH2 activity and partially compensates for its loss in different contexts . We herein demonstrated that H3K27me3 levels were maintained or elevated after TAS‐117 treatment (see the data in Figure B,C).…”
Section: Resultssupporting
confidence: 68%
“…Despite the development of selective EZH2 inhibitors in clinical trials, it is clear that the inhibition of EZH2 alone is insufficient for the complete disruption of PRC2 oncogenic functions . Although inconsequential to EZH2 functions, EZH1 can augment and maintain PRC2 activities . We herein clearly demonstrated that EZH1 contributes to an important compensatory mechanism in MM.…”
Section: Discussionmentioning
confidence: 59%
“…As expected, EZH1 occupancy was increased at other non-fibrotic genes to maintain H3K27me3 levels (Fig. 2g,h), supporting previous reports of EZH1 compensation for EZH2 deficiency 27-29 .…”
Section: Mainsupporting
confidence: 91%
“…Downregulation of EZH2 reduced the level of H3K27me3 in SKM-1 cells after intervention of EZH1 expression. EZH1 targets bivalent genes to sustain the self-renewal of stem cells in EZH2-de cient MDS [40]. Brie y, EZH2 regulated the level of H3K27me3, and EZH1 compensated for the effect of EZH2 deletion.…”
Section: Discussionmentioning
confidence: 99%